2008
DOI: 10.1177/0733464808321887
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Technology in Nursing Homes

Abstract: This study describes nursing homes' use of Minimum Data Set (MDS) software and identifies features that are available in the most commonly used software packages. Data came from the On-line Survey, Certification and Reporting system and a national survey of nursing home administrators (N = 2,899) conducted in 2005. Results show that 2,397 (82.7%) of nursing homes used third-party MDS software, and more than 85% of those facilities purchased the software from one of five vendors. Advanced features in the softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Future work will need to determine the optimum amount of information to be included on any transfer document and the ideal medium – paper or electronic - for its transmission, though electronic means are attractive. Many nursing homes use computers already to track Minimum Data Set figures 17 and may have the ability to implement advanced health information technology to facilitate electronic transfer of patient information. Moreover, the federal government has invested in projects through the National Health Information Network 18 to allow exchange of medical records and there is initial evidence that health information technology may ultimately improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will need to determine the optimum amount of information to be included on any transfer document and the ideal medium – paper or electronic - for its transmission, though electronic means are attractive. Many nursing homes use computers already to track Minimum Data Set figures 17 and may have the ability to implement advanced health information technology to facilitate electronic transfer of patient information. Moreover, the federal government has invested in projects through the National Health Information Network 18 to allow exchange of medical records and there is initial evidence that health information technology may ultimately improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The same 12 IT features were used in a previous study. 9 The IT questions in the survey confirmed that the facility had purchased commercial MDS software and the frequency of use of each feature. All questions regarding frequency of use had a 1 to 10 visual analog rating scale, assigning 1 for minimum usage (ie, not used at all) and 10 for maximum usage (ie, used all the time).…”
Section: Data Sourcementioning
confidence: 93%
“…9 This survey is relatively recent. However, it should be acknowledged that changes in health IT are occurring rapidly and may not be represented in the findings.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…MDS contains all core items that must be assessed. RAPs are used to form nursing care plans [31], provide diagnostic logic, and help evaluators to confirm the care required by residents, in accordance with the care planning of individual cases [20]. (2) TAI is composed of classification and grading assessment scales, an assessment scale of the required care for the aged, degradation and aging process charts, and a summary table of each unit.…”
Section: Resident-oriented Assessmentmentioning
confidence: 99%